Mimcry and the hoverflies - Azmeh, Salma (2000)
Hoverflies (Diptera: Syrphidae) vary widely in their mimetic associations, comprising wasp-mimetic, bee-mimetic and non-mimetic species. Social wasp mimics are dominated by 'imperfect mimics' which outnumber their supposed models (Hymenoptera: Vespidae) by large factors. The purpose of this thesis is to determine to what degree Batesian mimicry can account for these paradoxes, and to test alternative hypotheses for the evolution of the yellow-and-black patterns.